Effect of nano-scale texture pretreatment on wear resistance of WC/Co tools with/without TiAlN coated flank-face in dry turning of green Al2O3 ceramics. Issue 17 (1st December 2018) - Liu, Yayun; Deng, Jianxin; Liu, Lili; Wang, Wei; Meng, Rong; Duan, Ran; Ge, Dongliang; Li, Xuemu
Abstract: Advanced ceramics after sintering are almost processed by grinding or non-traditional machining. Nevertheless, these methods are limited by complexity of processing efficiency, tool wear and economic effectiveness. So machining green ceramics before sintering is introduced, it is environmentally friendly, efficient and cheap with high removal rate of materials. During dry turning green ceramics, flank-wear of tools and processing quality of compacts are two main elements to evaluate cutting performance of tools. The processing efficiency and economic effectiveness are mainly effected by the cutting performance of tools. In this paper, polished tool, tool with nano-scale textured flank-face, tool with TiAlN coating deposited on polished flank-face, and tool with TiAlN coating deposited on nano-scale textured flank-face were prepared. Effect of nano-scale texture pretreatment on wear-resistance of WC/Co tools with/without TiAlN coated flank-face was studied in turning of green Al2 O3 ceramics. Results displayed that nano-scale textures on the flank-face had prominent effects on the enhancement of flank-wear resistance of tools. Relevant mechanisms were explored that nano-scale textures exhibited "derivative cutting" to protect unworn face from abrasion, and nano-scale textures pretreated on the flank-face could enhance the adhesion strength between coating and matrix. These developed tools could also significantly improve the processing quality of machined surfaces.